Evaluation of central corneal epithelial thickness with anterior segment OCT in patients with type 2 diabetes mellitus - Yusufoglu, Elif; Kobat, Sabiha Gungor; Keser, Sinem (Springer, 2023)
Background This study aimed to evaluate the central corneal thickness (CCT) and central corneal epithelial thickness (CCET) in patients with Type 2 diabetes mellitus (DM), and the effect of the duration of diabetes, the degree of diabetic retinopathy (DR), and HbA1c level. Methods CCT and CCET values of 72 patients diagnosed with type 2 DM and 72 healthy individuals were measured by anterior segment optical coherence tomography. The eye tear function was evaluated with the Tear Break-up Time test (TBUT) and the Schirmer test. From the results of fundus examination, the diabetic patients were grouped as those without DR, non-proliferative DR, and proliferative DR. The disease duration and the HbA1c levels were recorded. Results In the diabetic patients, the mean CCT was determined to be thicker (p = 0.025), the CCET was thinner (p = 0.003), and the TBUT and Schirmer values were lower (p <0.001, p <0.001, respectively). The duration of diabetes and the HbA1c level was not found to have any statistically significant effect on these parameters (p >0.05). The presence of retinopathy had no significant effect on CCT, TBUT, and Schirmer values. The CCET was determined to be thinner in patients with retinopathy (p <0.001). Conclusions As the corneal epithelial thickness is reduced in patients with advanced diabetic retinopathy, corneal epithelial pathologies can be seen more often. Therefore, early and effective treatment can be started by taking into consideration the complications which may develop associated with the corneal epithelium following surgical procedures, especially those applied to the cornea.
Keywords: Diabetes mellitus; Central corneal thickness; Central corneal epithelial thickness; Diabetic retinopathy